Effect of the implementation of HIV/AIDS prevention and treatment policies on the mortality rate of people living with HIV in Guilin, China - Yan Feng; Ying Zhuo; Jie Tang; Guodong Zhang; Wuxiang Shi; Lingmi Zhou (Scientific Reports)
Abstract To analyze the changing trend of HIV/AIDS-related mortality before and after the implementation of the “Prevention and Treatment of HIV/AIDS” policy in Guilin from 1996 to 2020, and to evaluate its effect on HIV/AIDS prevention and treatment. The data of people with HIV reported in Guilin up to December 31, 2020, were obtained from the Chinese Center for Disease Control and Prevention (CDC), and the two rounds of “Prevention and Treatment of HIV/AIDS” policy intervention boundary points were taken in 2010 and 2015, respectively. The interruption time series (ITS) analysis was used to analyze the trend of HIV/AIDS-related mortality before and after the implementation of the HIV/AIDS Prevention and Treatment Project. From 1996 to 2020, the HIV/AIDS mortality rate decreased in Guilin, and the HIV/AIDS mortality rate of farmers was higher than the overall HIV/AIDS mortality rate. The ITS method analysis results showed that after the implementation of two rounds of “Prevention and Treatment of HIV/AIDS” policy, HIV/AIDS mortality rate showed a downward trend. Between 2010 and 2015, the overall decline in HIV/AIDS mortality rate exhibited a slope of -2.217 (P < 0.01). For individuals with an education level of high school or below, the decline in HIV/AIDS mortality rate during this period had a slope of -2.110 (P < 0.01). Among the farmer population, the decline in HIV/AIDS mortality rate from 2010 to 2015 was even more significant, with a slope of -2.510 (P < 0.01). From 2015 to 2020, the overall HIV/AIDS mortality rate continued to decline, showing a slope of -0.230 (P < 0.01). Between 2015 and 2020, for those with an education level of high school or below, the decline in HIV/AIDS mortality rate had a slope of -0.225 (P < 0.01). In contrast, the decline in HIV/AIDS mortality rate among farmers from 2015 to 2020 was steeper, with a slope of -0.319 (P < 0.01). From 2010 to 2020, the HIV/AIDS mortality rate in Guilin has shown a decreasing trend, indicating that the implementation of the “Prevention and Treatment of HIV/AIDS” policy has achieved good results.